2015
DOI: 10.1002/anie.201503417
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of GdIII‐Based Magnetic Resonance Contrast Agents for Molecular Imaging of Prostate‐Specific Membrane Antigen

Abstract: Magnetic resonance (MR) imaging is advantageous because it concurrently provides anatomic, functional, and molecular information. MR molecular imaging can combine the high spatial resolution of this established clinical modality with molecular profiling in vivo. However, as a result of the intrinsically low sensitivity of MR imaging, high local concentrations of biological targets are required to generate discernable MR contrast. We hypothesize that the prostate-specific membrane antigen (PSMA), an attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…The PC-3 PIP (PSMA pos ) and PC-3 flu (PSMA neg ) tumor cells were kindly provided by Prof. Dr. Martin Pomper (John Hopkins Institutions, Baltimore, USA) [32]. The cells were grown in RPMI cell culture medium supplemented with 10% fetal calf serum, L-glutamine, antibiotics, and puromycin (2 μg/mL) to maintain PSMA expression (Additional file 1) [33].…”
Section: Methodsmentioning
confidence: 99%
“…The PC-3 PIP (PSMA pos ) and PC-3 flu (PSMA neg ) tumor cells were kindly provided by Prof. Dr. Martin Pomper (John Hopkins Institutions, Baltimore, USA) [32]. The cells were grown in RPMI cell culture medium supplemented with 10% fetal calf serum, L-glutamine, antibiotics, and puromycin (2 μg/mL) to maintain PSMA expression (Additional file 1) [33].…”
Section: Methodsmentioning
confidence: 99%
“…16 MR imaging is reliant on intrinsic proton relaxation times of tissue and is widely used in clinical settings as an alternative to X-ray radiography, computed tomography, and nuclear modalities because it requires no ionizing radiation. To enhance tissue contrast, paramagnetic gadolinium(III) [Gd(III)] chelates are commonly utilized as contrast agents (CAs).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports of Gd(III)–nanoparticle formulations with high cell labeling efficiency and imaging efficacy. 1,2,5,10,2023 In particular, carbon-based nanomaterials bearing Gd(III) ions such as gadographene, gadofullerene, and gadonanotubes have been explored. 21,2427 However, a majority of these constructs have not enabled long-term cell labeling and fate mapping in vivo due to limited stability in biological media.…”
Section: Introductionmentioning
confidence: 99%
“…5 Other investigators have reported obtaining similar r 1 constants for peptide-based molecular agents with one and three Gd ions. 22 …”
Section: Resultsmentioning
confidence: 99%